Overcoming barriers to social inclusion in agricultural intensification: reflections on a transdisciplinary community development project from India and Bangladesh - Roth, Christian H.; Cosijn, Michaela; Carter, Lucy; Chakraborty, Arnab; Das, Mahanambrota; Hamilton, Serena H.; Jana, Alak Kumar; Lim-Camacho, Lilly; Majumdar, Subrata; Merritt, Wendy S.; Mishra, Pulak; Mishra, Rajeshwar; et al. (Oxford University Press, 2024)
We describe a research-for-development (R4D) strategy developed to address how investments and interventions in agricultural intensification as a means to achieve community development can be designed to be more socially inclusive and equitable. We draw on results from a 5-year project – Promoting socially inclusive and sustainable agricultural intensification in West Bengal (India) and southern Bangladesh (SIAGI). We reflect on a major pivot in the project’s strategy, from being primarily research-driven to placing community concerns and priorities at the centre with a shift towards Ethical Community Engagement (ECE). This became the foundational framework which guided the definition and undertaking of all subsequent activities – including a rethink of methods and concepts to develop tools and frameworks fit for purpose and local context, and inculcating a culture of reflexivity and mutual learning in the project. We show that creating the conditions for true participation, where project beneficiaries and non-government organizations are equal partners alongside researchers and government actors, and for co-learning using the ECE framework, sets the foundations for increased and potentially enduring social inclusion in agricultural intensification.